2012
DOI: 10.2478/v10181-012-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of humic-fatty acid preparation on selected haematological and biochemical serum parameters of growing rabbits

Abstract: In this study, we assessed the effect of a humic-fatty acid preparation (HFA) used in rabbit feed on certain haematological and biochemical serum parameters (the lipid profile and the Ca, P and Fe contents). A higher RBC, HGB and HCT values were observed in the groups that were given HFA. An increase in Fe concentrations were also noted. The total and LDL cholesterol were lower in the groups which received HFA than in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
(2 reference statements)
1
7
0
1
Order By: Relevance
“…Serum mineral levels (Ca, P, Mg and Fe) were not affected by ZnO + HNa treatments. HS appear to have metal-chelating effects and were reported to reduce levels of serum minerals in broilers (Rath et al 2006;Celik et al 2008;Samudovska and Demeterova 2010) and rabbits (Mista et al 2012), although this effect was not observed with HNa in weaned piglets (Trckova et al 2015). Significantly higher Zn levels in the serum of the ZnO 2.5 group reflected the higher Zn dietary intake in the group.…”
Section: Clinical Biochemical and Haematological Indicators Of Healtmentioning
confidence: 82%
See 2 more Smart Citations
“…Serum mineral levels (Ca, P, Mg and Fe) were not affected by ZnO + HNa treatments. HS appear to have metal-chelating effects and were reported to reduce levels of serum minerals in broilers (Rath et al 2006;Celik et al 2008;Samudovska and Demeterova 2010) and rabbits (Mista et al 2012), although this effect was not observed with HNa in weaned piglets (Trckova et al 2015). Significantly higher Zn levels in the serum of the ZnO 2.5 group reflected the higher Zn dietary intake in the group.…”
Section: Clinical Biochemical and Haematological Indicators Of Healtmentioning
confidence: 82%
“…The increase of HCT and HGB was also observed when HA was fed to broilers and rabbits (Ipek et al 2008;Mista et al 2012), although no data have as yet been reported from pigs. In our previous study, we observed non-significantly higher HCT and HGB when ZnO and HNa were fed to piglets challenged by E. coli (Trckova et al 2015).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…HS were reported to reduce serum minerals (P, Ca, Mg and Fe) in broilers (Rath et al 2006;Celik et al 2008;Demeterova et al 2009;Samudovska and Demeterova 2010), and rabbits (Mista et al 2012). A potential metal-chelating effect might be exerted by many reactive functional groups located in the structures of HS (Rath et al 2006).…”
Section: Haematological and Serum Biochemical Profilementioning
confidence: 99%
“…HS were described to decrease serum triacylglycerols and cholesterol levels in animals (Herzig et al, 2009;Samudovska and Demeterova 2010;Mista et al 2012;Ozturk et al 2012). After three weeks of HNa dietary treatment we observed only slightly (non-sig- 1 C = control with no supplementation; ZnO2.5 = supplemented with high prophylactic dose of ZnO (2.5 g/kg diet); HNa + ZnO1.7, HNa + ZnO1.5, HNa + ZnO1.0 = supplemented with HNa (20.0 g/kg diet) and 1.7, 1.5 and 1.0 g ZnO/kg diet, respectively The individual pig served as the experimental unit.…”
Section: Haematological and Serum Biochemical Profilementioning
confidence: 99%